Internalisasi Modal Budaya dalam Lingkungan Sekolah untuk Meningkatkan Minat Belajar Siswa di SMP Negeri 2 Baubau - Rosmawati Taherong; Edison; Samsaifil; Rindi; Herindang La Ida (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Students' low learning interest at SMP Negeri 2 Baubau is not solely associated with individual motivation but is also influenced by the weak internalization of academic cultural capital, as reflected in limited literacy practices, low classroom participation, and minimal student engagement in the learning process. This community service program aimed to enhance students' learning interest through strengthening school culture based on the internalization of cultural capital. The program employed a participatory approach consisting of preliminary observation, coordination with the school, and the implementation of three main intervention activities: contextual literacy development, the establishment of learning habits through discussions, presentations, and reflective learning, and the reinforcement of academic culture by promoting dialogic pedagogical relationships and recognizing students' active participation. The program outcomes indicated increased student engagement in classroom activities, improved reading and discussion habits, greater confidence in expressing ideas, and the creation of a more participatory learning environment. These findings demonstrate that strengthening cultural capital through sustained academic practices and supportive school culture can serve as an effective strategy for fostering students' learning interest